Beyond Local Crime Rate: How the Quantity and Quality of Social Interaction Influence Crime in Private Residences, Commercial Venues, and Public Spaces - Charron, Mathieu (Canadian journal of criminology and criminal justice, 2024)
Measuring crime rates is challenging in neighborhoods and other small geographic units. Its denominator, the local population, is strongly affected by mobility, with most city dwellers moving through many neighborhoods during the course of one day for different purposes. Under these conditions, the use of the residential population returns a flawed representation of the social interactions that can lead to crime. In this article, alternative ways to measure local population for crime rates are tested. We suggest that different measures of local population (residents, shoppers, workers, pedestrians, automobiles) yield specific and relevant information for the understanding of the concentration of crime in time and space and that crime place (private residences, commercial venues, and public space) should be taken into account in spatial analyses of crime. Results show that different local population measures carry complementary information on the quantity and quality of social interaction that can lead to crime.